Biomass Production Chlorella Vulgaris Buitenzorg Using Series of Bubble Column Photo Bioreactor with a Periodic Illumination - Wijanarko, Anondho; Dianursanti, Dianursanti; Muryanto, Muryanto; Simanjuntak, Josia; Kencana Wulan, Praswasti Pembangun Dyah; Hermansyah, Heri; Gozan, Misri; Soemantojo, Roekmijati Widaningroem (Makara Journal of Technology, 2008)
Chlorella vulgaris Buitenzorg cultivation using three bubble column photo bioreactors arranged in series with a volume of 200 mL for 130 hours shows an increase of biomass production of Chlorella vulgaris Buitenzorg up to 1.20 times and a decrease of the ability of CO2 fixation compared to single reactor at a periodic sun illumination cycle. The operation conditions on cultivation are as following: T, 29.0oC; P,1 atm.; UG, 2.40 m/h; CO2, 10%; Benneck medium; and illumination source by Phillip Halogen Lamp 20W /12V/ 50Hz. Other research parameters such as microbial carbon dioxide transferred rate (qco2), CO2 transferred rate (CTR), energy consumption for cellular formation (Ex), and cultural bicarbonate species concentration [HCO3] also give better results on series of reactor.